An NAD+ biosynthetic pathway enzyme functions cell non‐autonomously in C. elegans development. Issue 8 (10th May 2014) - Crook, Matt; Mcreynolds, Melanie R.; Wang, Wenqing; Hanna‐Rose, Wendy
<x xml:space="preserve">Abstract</x> Background: Disruption of cellular metabolite levels can adversely impact development. Specifically, loss‐of‐function of the C. elegans NAD+ salvage biosynthesis gene PNC‐1 results in an array of developmental phenotypes. Intriguingly, PNC‐1 and its functional equivalent in vertebrates are secreted, but the contributions of the extracellular enzymes are poorly understood. We sought to study the tissue‐specific requirements for PNC‐1 expression and to examine the role of the secreted isoform. Results: A thorough analysis of PNC‐1 expression did not detect expression in tissues that require PNC‐1 function. Limited expression of both the secreted and intracellular PNC‐1 isoforms provided function at a distance from the tissues with phenotypes. We also find that the secreted isoform contributes to in vivo PNC‐1 activity. Furthermore, uv1 cell survival has the most stringent requirements in terms of PNC‐1 expression pattern or level. Conclusions: Using careful promoter analysis and a restricted expression approach, we have shown that both the secreted and the intracellular PNC‐1 isoforms function cell non‐autonomously, and that the PNC‐1a isoform is functionally relevant in vivo. Our work suggests a model where PNC‐1 function is provided cell non‐autonomously by a mix of intra and extracellular activity, most likely requiring NAD+ salvage metabolite transport between tissues. Developmental Dynamics 243:965–976, 2014. © 2014 Wiley Periodicals, Inc.